2016
DOI: 10.1152/jn.00860.2015
|View full text |Cite
|
Sign up to set email alerts
|

The topography of alpha-band activity tracks the content of spatial working memory

Abstract: Working memory (WM) is a system for the online storage of information. An emerging view is that neuronal oscillations coordinate the cellular assemblies that code the content of WM. In line with this view, previous work has demonstrated that oscillatory activity in the alpha band (8-12 Hz) plays a role in WM maintenance, but the exact contributions of this activity have remained unclear. Here, we used an inverted spatial encoding model in combination with electroencephalography (EEG) to test whether the topogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
344
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(376 citation statements)
references
References 60 publications
30
344
2
Order By: Relevance
“…This location specificity of alpha-band dynamics is not limited to the hemifield level but also tracks the specific location that is attended (Foster, Sutterer, Serences, Vogel, & Awh, 2017; Rihs, Michel, & Thut, 2007). Indeed, recent studies have used inverted encoding models (IEMs) to reconstruct population-level channel tuning functions (CTFs) from the topographic distribution of alpha-band activity that reveal location-specific information during both covert attention tasks (Foster et al, 2017; Samaha, Sprague, & Postle, 2016) and the maintenance of spatial working memories (Foster, Bsales, Jaffe, & Awh, 2017; Foster, Sutterer, Serences, Vogel, & Awh, 2016). Together, these findings suggest a tight link between alpha-band dynamics and the focus of spatial attention, regardless of whether attention is directed toward external stimuli or toward remembered locations.…”
Section: Introductionmentioning
confidence: 99%
“…This location specificity of alpha-band dynamics is not limited to the hemifield level but also tracks the specific location that is attended (Foster, Sutterer, Serences, Vogel, & Awh, 2017; Rihs, Michel, & Thut, 2007). Indeed, recent studies have used inverted encoding models (IEMs) to reconstruct population-level channel tuning functions (CTFs) from the topographic distribution of alpha-band activity that reveal location-specific information during both covert attention tasks (Foster et al, 2017; Samaha, Sprague, & Postle, 2016) and the maintenance of spatial working memories (Foster, Bsales, Jaffe, & Awh, 2017; Foster, Sutterer, Serences, Vogel, & Awh, 2016). Together, these findings suggest a tight link between alpha-band dynamics and the focus of spatial attention, regardless of whether attention is directed toward external stimuli or toward remembered locations.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroscientific studies have established that the encoding of a subset of the available visual information into working memory can be measured by frequency-specific oscillations of subjects' electroencephalograms (EEGs) (17)(18)(19)(20). Specifically, the magnitude of suppression of alpha-band oscillations (8-13 Hz) measured across parieto-occipital channels as new information is held in working memory changes as additional information is loaded into working memory and hits an asymptote at a subject's working-memory capacity estimated from behavioral performance.…”
mentioning
confidence: 99%
“…Fernandino et al, 2016). Rather, it is important to examine the actual correspondence of the representations with additional RSA methods or dimensionality reduction and visualization techniques (e.g., Brouwer and Heeger, 2009;Foster et al, 2015). For example, in studying color representation in the early visual cortex, Brouwer and Heeger (2009) used principal components analysis (PCA) on the predicted voxel activation patterns and showed that the two main components present in the signal corresponded well to the actual organization of the colors in the color space they were using.…”
Section: Absolute Model Performancementioning
confidence: 99%
“…For example, in studying color representation in the early visual cortex, Brouwer and Heeger (2009) used principal components analysis (PCA) on the predicted voxel activation patterns and showed that the two main components present in the signal corresponded well to the actual organization of the colors in the color space they were using. Similarly, Foster et al (2015), who attempted to decode the orientation of lines that were held in visual working memory, showed that activity in the hypothesized angular channels, on which their encoding model was based, follows a graded pattern that peaks at their preferred orientation. In summary, we believe it is crucial to carefully examine the model predictions.…”
Section: Absolute Model Performancementioning
confidence: 99%
See 1 more Smart Citation